Denitrification Bioreactor in Northeast Iowa - Matthew Helmers; Carl Pederson (Hello World!, 2024)
Denitrification bioreactors for removal of nitrate in tile drainage are a new water quality technology that has rapidly gained interest in Iowa. A bioreactor is composed of an excavated trench filled with woodchips that are colonized by denitrifying bacteria. As drainage waters containing nitrate flow by these “good” bacteria, they convert the nitrate in the water to nitrogen gas. A critical component in evaluating the performance of these treatment systems is the documentation of nitrate-N reduction over a range in weather and flow conditions.